PENGARUH PENEMPATAN KERJA DAN MOTIVASI TERHADAP KINERJA KARYAWAN KELURAHAN LIMBANGAN WETAN KECAMATAN BREBES KABUPATEN BREBES - Solikhin Solikhin; Wuryati Wuryati (Jurnal Strategik, 2018)
This study aims to determine the effect of work placement and motivation on employee performance in Limbangan Wetan Village. From the results of the questionnaire and using the SPSS program using a confidence level of 95 percent (α / 2 = 0.05 / 2 = 0.025) and the degree of freedom Nk (14-2) the result of t work placement is equal to = 2.493 and the results of t count motivation is 2, 562 is greater than the table of 2.179 which indicates that partially the work placement and motivation variables have a significant influence on the performance variable. Calculation of Test F shows the results of 5.165 which means that together the independent variables of work placement and work motivation affect the performance variable. From the regression equation Y = 11.768 + 0.659X1 + 0.711X2 shows that the coefficient of X2 (motivation) is greater than the coefficient X1 (work placement) means that motivation has a more dominant influence on performance.